Acute epididymo-orchitis complicating Streptococcus pneumoniae bacteremia in an adult smoker and alcoholic with community acquired pneumonia - Ibrahim, TM; Letchumanan, MN (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Although hematogenous acute epididymo-orchitis complicating Gram negative bacteremia, tuberculosis and brucellosis have been reported in medical literature, there is paucity of report on acute epididymo-orchitis complicating Streptococcus pneumoniae bacteremia. CASE REPORT: We report the case of hematogenous acute epididymo-orchitis from S. pneumoniae bacteremia in an adult chronic cigarette smoker and alcoholic with community acquired pneumonia. CONCLUSION: We recommend that acute epididymo-orchitis should be remember as a sequel of S. pneumoniae bacteremia especially in adult males with immune suppression DOI: http://dx.doi.org/10.3126/ijim.v1i2.7411 Int J Infect Microbiol 2012;1(1):80-83